Optimizing VAT Planning to Enhance Tax Efficiency in Indonesia: Mengoptimalkan Perencanaan PPN untuk Meningkatkan Efisiensi Perpajakan di Indonesia - Istighfara, Risna Cahya; Biduri, Sarwendah (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of tax planning strategies on VAT reporting and payment efficiency for PT. Fajar Putra Plasindo. Using a quantitative approach, it analyzes VAT data from 2021 to assess the effectiveness of tax planning in optimizing the company's tax burden. Results show a tax burden efficiency of Rp. 38,783,510, highlighting the benefits of strategies such as purchasing taxable goods/services from registered taxpayers and delaying tax invoice reporting. These findings emphasize the importance of proactive tax planning for minimizing tax liabilities and improving cash flow management, ultimately enhancing financial performance and regulatory compliance for companies operating in similar contexts. Highlight: Tax planning optimizes VAT burden with strategic purchasing and reporting. Improved financial performance through effective tax planning strategies. Enhances regulatory compliance, minimizing risks and penalties for businesses. Keywoard: Tax Planning, VAT Reporting, Efficiency, Financial Performance, Regulatory Compliance